Tools for structured team communication in pre-registration health professions education: a Best Evidence Medical Education (BEME) review: BEME Guide No. 41. (2nd October 2016) - Buckley, Sharon; Ambrose, Lucy; Anderson, Elizabeth; Coleman, Jamie J.; Hensman, Marianne; Hirsch, Christine; Hodson, James; Morley, David; Pittaway, Sarah; Stewart, Jonathan
Abstract: Introduction: Calls for the inclusion of standardized protocols for information exchange into pre-registration health professions curricula have accompanied their introduction into clinical practice. In order to help clinical educators respond to these calls, we have reviewed educational interventions for pre-registration students that incorporate one or more of these ?tools for structured communication?. Methods: Searches of 10 databases (1990?2014) were supplemented by hand searches and by citation searches (to January 2015). Studies evaluating an intervention for pre-registration students of any clinical profession and incorporating at least one tool were included. Quality of included studies was assessed using a checklist of 11 indicators and a narrative synthesis of findings undertaken. Results: Fifty studies met our inclusion criteria. Of these, 21 evaluated the specific effect of a tool on educational outcomes, and 27 met seven or more quality indicators. Conclusions: Pre-registration students, particularly those in the US, are learning to use tools for structured communication either in specific sessions or integrated into more extensive courses or programmes; mostly 'Situation Background Assessment Recommendation' and its variants. There is some evidence that learning to use a tool can improve the clarity and comprehensiveness of student communication, their perceived self-confidence and their sense of preparedness for clinical practice. There is, as yet, little evidence for the transfer of these skills to the clinical setting or for any influence of teaching approach on learning outcomes. Educators will need to consider the positioning of such learning with other skills such as clinical reasoning and decision-making.